(untitled) (ResearchJet Journal of Analysis and Inventions, 2021)
Uzbek phraseological units, reflecting elements of culture, are associated with many areas of human life. At the same time, they can be connected both with the everyday and empirical experience of the people, and with the sphere of material culture, with the historical experience of the people, etc. In the Uzbek language, as in many other languages, there are enough phraseological units with "color" components.